NCOA4 Regulates Iron Recycling and Responds to Hepcidin Activity and Lipopolysaccharide in Macrophages - Cole A. Guggisberg; Juyoung Kim; Jaekwon Lee; Xiaoli Chen; Moon-Suhn Ryu (MDPI AG, 2022)
Macrophages, via erythrophagocytosis, recycle iron from effete erythrocytes to newly developing red blood cells. Conversion of potentially cytotoxic levels of iron from its heme into nonheme form during iron recycling is safely accomplished via coordinated regulations of cellular iron transport and homeostasis. Herein, we demonstrate the roles and regulation of NCOA4 (nuclear receptor coactivator 4)-mediated ferritinophagy in macrophages after erythrophagocytosis using the mouse macrophage cell line J774 cells. Ferritin in J774 cells increased with the rise of nonheme iron by erythrocyte ingestion and declined when total cellular iron contents subsequently decreased. NCOA4, a selective autophagic cargo receptor for ferritin, was responsible for the control of cellular ferritin and total iron contents at the later stage of erythrophagocytosis. A hepcidin analog, which limits the flux of iron through iron-recycling by inhibiting iron export at the plasma membrane, repressed NCOA4 expression and led to accumulation of ferritin in the mouse macrophages. Transcriptome analyses revealed a functional association of immune response with NCOA4-dependent gene expressions, and we confirmed repression of Ncoa4 by lipopolysaccharide (LPS) in J774 cells and the spleen of mice. Collectively, our studies indicate that NCOA4 facilitates cellular ferritin turnover and the release of iron by macrophages after erythrophagocytosis and functions as a regulatory target for molecular signals of systemic iron overload and inflammation. These identify macrophage NCOA4 as a potential therapeutic target for disorders of systemic iron dysregulation, including anemia of inflammation and hemochromatosis.